3D Surface Profile and Color Stability of Tooth Colored Filling Materials after Bleaching - Irawan, Bryant Anthony; Irawan, Stacey Natalie; Masudi, Sam’an Malik; Sukminingrum, Nining; Alam, Mohammad Khursheed (Hindawi Publishing Corporation, 2015)
This study aims to evaluate the effects of vital tooth bleaching with carbamide peroxide home bleaching and in-office bleaching on the color stability and 3D surface profile of dental restorative filling materials.Thirty discs (